Sodium Isopropyl Xanthate Degradation by Advanced Oxidation Processes - Cifuentes-Molina, G (2013)
This paper presents the results obtained by different oxidative processes when an aqueous solution containing sodium isopropyl xanthate is treated; this reagent is used in the flotation of copper minerals. The advanced oxidation processes used are UV photolysis, direct electrolysis and photoelectrooxidation. The solutions used containing sodium isopropyl xanthate were adjusted to the following concentrations: 6, 8, 10, 25 and 40 mg L-1. The results show that the three oxidation processes proved to be suitable for the destruction of xanthate, with the following maximum destruction efficiencies: 76% for electrolysis, 95% for UV photolysis and 99% for photoelectrooxidation. © 2012 Elsevier Ltd. All rights reserved.